Oxidation behaviour of low carbon steel in natural water - Mohammed Misbahul, Amin; W. B., Wan Nik; Kamaruzzaman, Yunus (Oriental Science Publishing Co, 2009)
Link to publisher's homepage at http://www.orientjchem.org/